Transient Chaos Complex Dynamics on Finite Time Scales - Lai, Ying-Cheng; Tél, Tamás (Applied Mathematical Sciences, 2011)
This book represents the first comprehensive treatment of Transient Chaos. It gives an overview of the subject based on three decades of intensive research. One special emphasis is on applications, and the fact that certain interesting dynamical phenomena can be understood only in the framework of transient chaos. Specific topics treated include basic concepts and characterization of transient chaos, crises, fractal basin boundaries, chaotic scattering, noise-induced chaos, chaotic advections and the spreading of pollutants in fluid flows, quantum chaotic scattering, spatiotemporal chaotic transients and turbulence, controlling transient chaos, and analysis of transient chaotic time series, etc. Materials in the book reflect the most recent advances in the field. Case studies and examples are included in each chapter with relevant experimental evidence wherever appropriate. The book is intended for researchers and graduate students in Physics, Engineering, Applied Mathematics, and Biomedical Sciences. Ying-Cheng Lai is a Professor of Electrical Engineering and Professor of Physics at Arizona State University, USA and a Sixth Century Chair in Electrical Engineering at the University of Aberdeen, UK. Tamás Tél is a Professor of Physics at Eötvös University, Budapest, Hungary.